Elaboración de un modelo empresarial para que las PyME del sector de bebidas y alimentos logren incrementar su ciclo de vida en la ciudad de Bogotá (2017)
The objective of this article, is to identify and analyze the factors that allowed SMEs in the food and beverage sector to grow and stay in the market for a higher time than five years, to be able to propose a characterization that serves as a reference for other companies that are beginning, or which have problems of sustainability. For this purpose, different tools, such as observation techniques, in-depth interviews, and statistical techniques were used to analyze the possible factors that allow the durability of SMEs over time. In the first instance, an analysis of the contribution of the different national sub-sectors to the growth of production in the Colombian industrial sector was made, in which the food and beverage sector could be identified as the most representative. Subsequently, a sample of the SMEs of that industry was established, which were interviewed in depth to identify the key success factors. The end result is a sustainable business model so that entrepreneurs can route their organization to more competitive fields, and not only be conform to a balance of their incomes and expenses, but also, they can be able to get sustainable economic growth to achieve competitiveness in their sector and thus overcome the stage of maturity in the life cycle of an organization.